The Roles of Romantic Beliefs and Imagined Interaction in Unrequited Love. (December 2022) - Hu, Mu; Zhang, Bingqing; Shen, Yinghe; Guo, Jing; Wang, Shuwen
The present study examined the roles of people's romantic beliefs and imagined interactions in unrequited love. Two hundred and twenty five Chinese college students participated in a survey study. More idealized romantic beliefs were associated with stronger unrequited love. Men's unrequited love was stronger than women's. Would-be lovers who had imagined interactions with beloved ones had stronger unrequited love in contrast to those who didn't. Unrequited love and romantic beliefs were both positively related to the imagined interaction attributes of frequency and valence and the functions of compensation and relationship maintenance. Frequency of imagined interactions positively mediated the relationship between romantic beliefs and unrequited love.